The big sleep - Chandler, Raymond, 1888-1959 (Vintage crime/Black Lizard., 1992)
When a case of blackmail involving the daughter of a California millionaire leads to murder, the inimitable Philip Marlowe is stirred into action as he becomes embroiled in a troublesome case of extortion complicated by kidnapping, pornography, seduction, and murder.